THE RELATIONSHIP BETWEEN NUMERICAL ABILITIES, STUDENTS PERCEPTION OF MATHEMATICS, AND SOCIAL ECONOMIC PARENTS TOWARD MATHEMATICS LEARNING OUTCOMES OF STUDENTS IN CLASS X TITL OF SMK - Dody Okkosila; Aris Thobirin (Universitas Ahmad Dahlan, 2018)
The results of interviews in SMK Negeri 1 Pleret country found some problems that numerical ability is still lacking, assuming that mathematics is a difficult lesson or complicated. Social, economic parents are still less, such as inadequate facilities, and the result of student learning mathematics is still low. This research aims to determine the presence or absence of positive and significant the relationship between numerical ability, student’s perception of mathematics, and social, economic parents to mathematics learning outcomes in students class X TITL of State Vocational High School 1 Pleret (SMK Negeri 1 Pleret) Bantul in Even Semester in Academic Year of 2017/2018. This research population was the students of X TITL of SMK Negeri 1 Pleret Bantul in 2017/2018, consisting of class X TITL A, X TITL B, X TITL C, totaling 101 students. Class X TITL B was selected as a class of research samples with a random sampling technique. The writer uses the questionnaire method to collect the data of student's perception of mathematics and social, economic parents, and test method to get data of numerical ability and the resulting learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear Regression analysis to analyze the data. The results showed a positive and significant relationship between numerical ability, students' perception of mathematics, and social, economic parents with mathematics learning outcomes in students class X TITL of SMK Negeri 1 Pleret Bantul in Even Semester in Academic Year of 2016/2017. It is showed by Fcount Ftable is with and with , with , and , dan .